2020
DOI: 10.3389/fspor.2020.00024
|View full text |Cite
|
Sign up to set email alerts
|

“I Didn't Make It, but…”: Deselected Athletes' Experiences of the Talent Development Pathway

Abstract: The experiences of youth athletes on specialized talent development pathways has received considerable attention in both the media and literature. Despite the low conversion of pathway entrants into senior athletes, the experiences of deselected athletes have received less attention. The purpose of this study therefore was to explore the talent pathway experiences of youth athletes who were deselected from a pathway and to consider how those experiences influenced their life post deselection. Ten participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 73 publications
4
27
0
Order By: Relevance
“…A wide variety of personal and life skills were attributed to academy involvement, especially: a strong work ethic, discipline, resilience, self-regulation, determination, a willingness to reflect, interpersonal skills and team work, (social) confidence, good manners and a respectful attitude. These findings add to the existing evidence that TIDS can be conducive towards positive development (e.g., Henriksen, 2010;Jones & Lavallee, 2009;Jørgensen et al, 2020;Strachan & Davies, 2015;Williams & MacNamara, 2020). However, as recent studies (e.g.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…A wide variety of personal and life skills were attributed to academy involvement, especially: a strong work ethic, discipline, resilience, self-regulation, determination, a willingness to reflect, interpersonal skills and team work, (social) confidence, good manners and a respectful attitude. These findings add to the existing evidence that TIDS can be conducive towards positive development (e.g., Henriksen, 2010;Jones & Lavallee, 2009;Jørgensen et al, 2020;Strachan & Davies, 2015;Williams & MacNamara, 2020). However, as recent studies (e.g.…”
Section: Discussionsupporting
confidence: 82%
“…As such, the moral justification and healthiness of entering youths into very intensive training environments has increasingly been questioned (e.g., Bergeron et al, 2015;Sabato et al, 2016). Perhaps as a result, there is a growing call for elite youth sport contexts to promote healthy performance and positive personal development (e.g., Mathorne et al,2020;Williams & MacNamara, 2020).Indeed, advocating a holistic ecological approach and focusing specifically on athletic talent development environments (ATDEs), Henriksen and Stambulova (2017) pose that successful environments are not only good at nurturing athletes to become successful elite senior athletes, but should also take a whole-person approach and develop athletes' competencies and skills that allow them to meet the challenges they face both in sport and other spheres of their life. Such an approach would also ensure youth athletes have requisite skills to be successful after the inevitable (and for many early) exit from sport (e.g., Bergeron et al, 2015;Grey-Thompson, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It is also possible that as a duty of care, the Academy Director and age group coaches may have utilized their network to assist players in continuing to play academy-level soccer. Such processes have previously been reported by deselected athletes across other sports (Williams and MacNamara, 2020 ). We propose that previous exposure to a TD programme may explain the prevalence of reselection we observed.…”
Section: Discussionsupporting
confidence: 75%
“…Williams and MacNamara ( 2020 ) found that high-potential young athletes who were deselected reported that the experience of the talent pathway provided the foundations for future success in other sports, careers, or education opportunities. The talent pathway can provide an environment that develops valuable constructs, (i.e., professionalism and positive performance behaviours), psychobehavioural skills (i.e., social awareness and effective communication), and personal responsibility (i.e., self-motivation and personal drive/desire) which can crossover to alternative domains outside of sport and prove advantageous (Williams and MacNamara, 2020 ). Similarly, Neeley et al ( 2018 ) identified that deselection from the talent pathway can be accompanied by subsequent personal growth experiences.…”
Section: Optimising Early Engagement In a Specialised Pathwaymentioning
confidence: 99%
“…The authors noted that, despite not progressing, deselected athletes experienced an enhanced sense of personal strength, developed closer social relationships, and recognised new and alternative opportunities. Therefore, it is possible that if structured appropriately, players can have many positive experiences during their time in football academies leading to the development of multiple skills and behaviours that are transferable to many other parts of their lives (Williams and MacNamara, 2020 ).…”
Section: Optimising Early Engagement In a Specialised Pathwaymentioning
confidence: 99%